Factor VII Tokushima: the first case of factor VII Cys22Gly with the development of myocardial infarction in the proband receiving recombinant factor VIIa replacement therapy. Issue 8 (December 2015) - Shigekiyo, Toshio; Sekimoto, Etsuko; Shibata, Hironobu; Ozaki, Shuji; Okumura, Takanobu; Fujinaga, Hiroyuki; Shibata, Hiroshi; Aihara, Ken-ichi; Akaike, Masashi
Abstract : An 81-year-old man was referred to our department because of suspected factor VII (FVII) deficiency. His FVII activity was under 1%, whereas the FVII activity levels of his son and granddaughter were 65 and 109%, respectively. The nucleotide at position 3886 of his FVII gene was homozygous for G. A single T to G substitution results in the replacement of wild-type Cys at residue 22 by Gly. His son was heterozygous for G and T at position 3886, whereas his granddaughter was homozygous for wild-type T. These results suggest that he was homozygous for FVII Cys22Gly. He underwent radiofrequency ablation (RFA) for hepatocellular carcinoma, receiving 20 μg/kg of recombinant FVIIa prior to RFA and 10 μg/kg of recombinant FVIIa twice after RFA. He showed no bleeding tendency; however, a myocardial infarction was diagnosed and percutaneous coronary intervention was performed.